Does the Special Allocation Fund Reduce Rural Poverty? - Sinarwati, Ni Kadek; Sihombing, Pardomuan Robinson (P4W IPB, 2024)
This study aims to analyze the effect of special allocation funds for thematic poverty reduction assignments in the fields of water, sanitation, and the field of settlement and housing on poverty in rural areas. The data collected by secondary data is number of poor people in rural areas is accessed through the BPS website, and special allocation funds for thematic poverty reduction assignments in the fields of water, sanitation, and settlement and housing are collected by accessing the Simtrada website (Information System Transfer to Regions and Village Funds) https://djpk.kemenkeu.go.id//simtrada/. The population of 34 provinces and the sample of 25 provinces in Indonesia that experienced a decrease in rural poverty were analyzed in this research. The data were analyzed by multiple regression analysis techniques. The results showed that special allocation funds for thematic poverty reduction assignments in the water sectors, and in the field of sanitation sector, did not significantly affect poverty reduction, (sig p-value 0.461>0.05 and sig p-value 0.751 > 0.05 respectively). The value of special allocation funds for thematic poverty reduction assignments in the field of the housing sector had a significant effect on reducing rural poverty (sig p-value (0.007< 0.05). This study recommends that poverty reduction funds in rural areas, especially in the field of housing, continue to be distributed and managed appropriately, so that poverty in rural areas is alleviated.